Macronutrient uptake, transport and use efficiency in seedlings of Pochota fendleri produced in different substrates and crushed Brazil nut capsules (Bioscience Journal, 2020)
Seedlings produced in containers can be influenced by the materials used in the substrate, which affects the robustness of the plants and, indirectly, the time required for transplanting and for the plants to become established in the field. The aim of this study was to determine the chemical properties of different materials and on the absorption of macronutrients in Pochota fendleri seedlings (cedro-doce). The treatments were: sand (Sa), soil (So), sand+soil (Sa+So), and sand+soil+crushed Brazil nut capsules (Sa+So+CNC). The growth and macronutrient content were evaluated at 60 days after thinning. The amount of macronutrients in the substrate increased with the addition of crushed Brazil nut capsules. The use of different materials for the substrate, particularly Sa+So+CNC, had a positive influence on the morphological characteristics of seedlings, which ensuring high rates of establishment and survival after outplanting, making commercial reforestation with Pochota fendleri attractive.